(untitled) (Research, Society and Development, 2023)
Objective: To identify the prevalence of postpartum depression symptoms and associated factors in women who had children in the last 12 months of 2019 in the city of Montes Claros/MG. Method: Analytical and cross-sectional exploratory study, composed of 236 women who gave birth in the last 12 months of 2019. For sample calculation, a prevalence of 20% was adopted. Household interviews were conducted, and the Edinburgh Postnatal Depression Scale was applied. Descriptive analyzes and bivariate comparisons were performed using the chi-square test. In the multivariate model, the variables that presented P value <0.20 were selected, included in the Poisson Regression. The results were presented in tables containing P value, β, Exponential of β and confidence interval (95%). Results: The prevalence of depressive symptoms was found in 32.2% of the interviewees. The main risk factors for the emergence of PPD can be identified, such as: absence of a partner, low family income, low level of education, lower number of prenatal consultations performed and number of children. Final considerations: A high prevalence of symptoms was identified, even higher than in studies cited in this article, however, it characterized several risk factors that associated with pregnant women or with a child under one year old, collaborate for the development of depression- post childbirth.